2013
DOI: 10.1007/978-3-642-38965-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment for Epstein–Barr Virus Infection and Related Cancers

Abstract: Epstein-Barr virus (EBV) was the first herpes virus described as being oncogenic in humans. EBV infection is implicated in post-transplant lymphoproliferative diseases (PTLD) and several other cancers in non-immunocompromised patients, with more than 200,000 new cases per year. While prevention of PTLD is improving, mainly based on EBV monitoring and preemptive tapering of immunosuppression, early diagnosis remains the best current option for the other malignancies. Significant progress has been achieved in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
0
9
0
1
Order By: Relevance
“…Three patients (0.9%) developed PTLD out of 323 adult patients who underwent liver transplant and all 3 were cases of late-onset [21]. Overall, as already reported in the literature [2,7,8], the incidence rates of PTLD reported in our review were quite broad (0.5-2.9 in kidney and 0.8-3.6 in liver), probably due to the different sizes of the examined cohorts (Table 1).…”
Section: Ptld Incidence After Kidney or Liver Transplantmentioning
confidence: 38%
See 4 more Smart Citations
“…Three patients (0.9%) developed PTLD out of 323 adult patients who underwent liver transplant and all 3 were cases of late-onset [21]. Overall, as already reported in the literature [2,7,8], the incidence rates of PTLD reported in our review were quite broad (0.5-2.9 in kidney and 0.8-3.6 in liver), probably due to the different sizes of the examined cohorts (Table 1).…”
Section: Ptld Incidence After Kidney or Liver Transplantmentioning
confidence: 38%
“…In one cohort of children with liver transplants, valganciclovir was used to treat transplant patients showing detectable EBV-DNA. Data showed that long-term treatment (8 months) achieved undetectable EBV-DNA in 47.6% of patients, 60% of whom maintained response when off therapy [8,81].…”
Section: Strategies For Treatment Of Ebv-driven Ptldmentioning
confidence: 97%
See 3 more Smart Citations